Islamic economics perspective on unemployment in Lampung province: the effect of education, minimum wage and economic growth / Retnika Anggi, Madnasir and Yulistia Devi - Anggi, Retnika; Madnasir, M; Devi, Yulistia (Universiti Teknologi Mara Selangor, 2023)
The Minimum Wage of Bandar Lampung City has always increased but unemployment has fluctuated. The level of economic growth that has increased does not always result in a decreasing unemployment rate, and vice versa, unemployment is still increasing. This research method is quantitative research with path analysis techniques. The data used in this research is secondary data with panel data analysis by bringing together from 15 city districts in Lampung province using eviews 9 as a data analyzer. In this study, there are three structural equations and three test models carried out to test the structural equations, namely the pooled least square method, the fixed effects method, the random effects method with the model selection test, namely the brake or random effects method. Based on the results of panel data analysis and hypothesis testing, it can be concluded that simultaneously (f test) education, minimum wage and economic growth have a significant effect on unemployment with a probability value of 0.000030 <0.05. Partial analysis result (T test) Education has a significant effect on unemployment with a value of 0.00 < 0.05. While the results of partial analysis (T test) city minimum wage and economic growth have no effect on unemployment with a value of 0.08> 0.05.